THE EFFECTIVENESS OF E-COMIC MEDIA UTILIZATION BASED ON CONTEXTUAL TEACHING AND LEARNING (CTL) TO INCREASE LEARNING MOTIVATION OF GRADE VIII STUDENTS - Meiyelti, Meiyelti; Puyanti, Puyanti; Oktavia, Rani (Department of Science Education, 2024)
This research aims to determine the effectiveness of the use of e-comic media based Contextual Teaching and Learning (CTL) in improving motivation to learn natural sciences students of Class VIII SMPN 40 Padang. In this research, the control class was given conventional learning, while the experimental class was given learning with E-comic media based on Contextual Teaching and Learning (CTL). This type of research is quasi Experimental Research with Pretest-Posttest Nonequivalent Control Group Design. Sampling technique using Purposive Sampling. The sample in this study was Class VIII.1 (Control class) and Class VIII.2 (experimental class)with a total of 64 students. The instrument in this study is a questionnaire of motivation to learn science. The results showed the N-Gain value in the control class was -0.08 and the experimental class was 0.06 and the low interpretation, with the low interpretation of the N-Gain causing no significant effect between learning using CTL based e-comic media and conventional learning models. As the results of the hypothesis test obtained that the tcount gainscore is 0.983, while the ttable is 1.999 at the significance level α = 0.05 with dk = 62. So it can be concluded that tcount < ttable (Ha is rejected and Ho is accepted) which means that the use of e-comic media based on Contextual Teaching and Learning (CTL) is not effective in increasing students science learning motivation on the material of the human digestive system.